Assessment of large critical electric field in ultra-wide bandgap p-type spinel ZnGa2O4. (22nd February 2023) - Chi, Zeyu; Tchelidze, Tamar; Sartel, Corinne; Gamsakhurdashvili, Tsotne; Madaci, Ismail; Yamano, Hayate; Sallet, Vincent; Dumont, Yves; Pérez-Tomás, Amador; Medjdoub, Farid; Chikoidze, Ekaterine
Abstract: The spinel zinc gallate ZnGa2 O4 stands out among the emerging ultra-wide bandgap (∼5 eV) semiconductors as the ternary complex oxide with the widest gap where bipolar conductivity has been demonstrated. For power and energy electronics, a fundamental property of the material is its critical electric field ( E CR ) although, for ZnGa2 O4, is yet unknown. In this work, highly resistive p -type ZnGa2 O4 thin films on sapphire and Si substrates were grown by metal organic chemical vapor deposition to determine both, the remote acceptor concentration and vertical breakdown voltage. Hall Effect measurements confirmed a low carrier concentration at room temperature of ∼10 11 cm −3 . From vertical metal-semiconductor-metal structures the average E CR has been estimated to be of at least 5.3 MV cm −1, which already is significantly larger than the one of SiC and GaN.